Passions and Pain: Lucy’s Punitive Death in Dracula - Huang, Chiung-Ying (International Journal of Language and Literary Studies, 2024)
This paper argues that the portrayal of a woman’s body in pain can be seen as an intense form of passion that transcends conventional boundaries. This ineffable passion may encompass not only the physical experience of pain but also the release of repressed desires. In Gothic texts, such as Dracula, the depiction of female suffering often serves to highlight the liberation of female eroticism from societal constraints. Lucy’s transformation into a vampire, and the subsequent pain she endures, can be interpreted as a metaphor for the liberation of her suppressed desires. Her suffering thus becomes a space where her passions, previously constrained by Victorian norms, are expressed and made manifest. Dracula exemplifies how Gothic literature can intertwine themes of passion, pain, and punishment to address larger social and cultural issues. The novel’s portrayal of Lucy’s suffering serves both as a dramatic narrative device and as a commentary on the persistent challenges of patriarchal control and female subjugation. The ongoing relevance of these themes underscores the enduring struggle for gender equality and the need to critically engage with representations of female suffering in literature.